The making of a maritime explorer: the early career of Matthew Flinders. (2nd January 2016) - Morgan, Kenneth
ABSTRACT: This article examines the early career of Matthew Flinders (1774–1814) to determine the ways in which his training as a navigator, hydrographer and cartographer prepared him for undertaking the first circumnavigation of Australia in the Investigator between 1801 and 1803. Two main questions are answered in relation to this theme. First, why was such a young naval officer as Flinders (he was 26) selected to lead such an important voyage of discovery? And, second, in what ways did the choice of Flinders as the commander of the Investigator reflect the training he had received? The article argues that the making of Flinders as a maritime explorer was forged through his successive nautical achievements in the 1790s, partly in relation to William Bligh's second breadfruit voyage to the Pacific in 1791–1792 and partly in relation to voyages along the coasts of New South Wales and Van Diemen's Land that Flinders undertook between 1795 and 1800. During that period, Flinders jointly discovered Bass Strait and circumnavigated Van Diemen's Land: these were the two most significant geographical discoveries in Australia since the era of Captain Cook. The article shows that when he returned from Port Jackson to London in 1800, Flinders was the most experienced candidate with knowledge of Australian waters who was available to lead the Investigator expedition. It also argues that Flinders placed himself in a highly favourable position to be selected as the leader of the circumnavigation through demonstrating to Sir Joseph Banks, his patron, that he had a thorough, up-to-date knowledge of what needed to be discovered about Australia through maritime exploration. Throughout, there will be an emphasis on the nautical skills Flinders acquired rapidly as a young midshipman and lieutenant and on his determination and initiative to devote his career to Australian discovery.